AN EVALUATION ON LEVELS OF KNOWLEDGE, ATTITUDE AND BEHAVIOR OF PEOPLE AT 65 YEARS AND ABOVE ABOUT ALTERNATIVE MEDICINE LIVING IN ANKARA - Özer, Özlem; Şantaş, Fatih; Yıldırım, Hasan Hüseyin (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The aim was to determine the knowledge, attitude and behavioral levels of people at and above 65 years of age, living in Ankara (Turkey) about alternative medicine. The study was carried out between March – April 2010 through survey application of 200 participants by selective random sampling from the population. Data obtained as a result of the survey were analyzed by SPSS program. The study revealed that 83.5% of the participants believed in alternative therapy methods but 16.5% of them did not. It is concluded that herbal therapy methods are the most frequently used methods with a 63% rate among other alternative therapy methods. When status of the participants was analyzed it was found that it was found that 69% received the information about alternative medicines from their family while 53.5% received it from television This study revealed that alternative medicine is profoundly used by people above 65 years of age in Ankara.